Integrated surgical intervention for intradural extramedullary hemangioblastoma of the cervical spine: a case report and literature review - Wang, Yao; Zhu, Qing; Chen, Ailin; Dai, Chungang; Xu, Longjiang; Sheng, Minfeng; Huang, Qiang; Lan, Qing; Mu, Qingchun; Li, Rujun (Frontiers in Oncology, 2024)
IntroductionThe incidence of hemangioblastoma is low, constituting only 1-5% of all spinal cord tumors. Specifically, intradural extramedullary hemangioblastoma without Von Hippel-Lindau syndrome represents an exceedingly rare condition.MethodsWe report the first documented case of cervical intradural extramedullary hemangioblastoma in China. A 53-year-old male patient presented with a 3-year history of mild right hemiplegia, segmental muscle strength and sensation impairment, and a positive pyramidal tract sign. MRI showed an abnormal oval signal focus in the intradural and extramedullary region at the C6-C7 vertebral level. Before surgery, angiography was performed to identify the supplying arteries and draining veins. Subsequent interventional therapy achieved over 90% occlusion of blood vessels, creating optimal conditions for complete resection of the spinal tumor.ResultsThe patient demonstrated satisfactory postoperative recovery with significant restoration of sensory and motor functions. Pathological examination showed a significant upregulation of CD31 in tumor cells and a substantial presence of the neuro-specific marker S100 in the tumor stroma, consistent with the diagnostic criteria for spinal hemangioblastoma.ConclusionThe rarity of cervical intradural extramedullary hemangioblastoma without Von Hippel-Lindau syndrome was reaffirmed by a comprehensive review of the existing literature. Complete tumor resection remains the optimal approach for managing this uncommon condition, generally resulting in a favorable prognosis. Traditional open fenestration surgery is linked to elevated risks of bleeding and trauma. Meanwhile, endovascular injection of embolic agents may lead to residual lesions and an increased risk of recurrence. Therefore, we recommend a one-time combined treatment conducted in a hybrid operating room to achieve complete resection and effectively reduce intraoperative bleeding risk. Despite presenting challenges and requiring high proficiency, we still recommend this type of combined surgery as a suitable therapeutic option for such diseases.